An artificial magnetic conductor‐backed monopole antenna to obtain high gain, conformability, and lower specific absorption rate for WBAN applications. Issue 12 (14th September 2020) - Hazarika, Bidisha; Basu, Banani; Nandi, Arnab
Abstract: In this article, a dual‐layered, compact, high gain, wearable, low specific absorption rate (SAR) Artificial Magnetic Conductor (AMC) integrated antenna operating in the ISM band is presented for WBAN application. This antenna comprises of partially grounded monopole integrated with slotted periodic AMC layer to enhance the radiation performances. The slotted unit‐element structure has obtained zero‐reflection phase and alters different material parameters. The integrated antenna has achieved maximum gain of 7.4 dB which is 82% more than that of the monopole as the periodic AMC has transformed the out of phase EM radiation along main beam direction. The integrated antenna offers conformability against various bending radii owing to in‐phase reflection property. After inclusion of AMC below the monopole, the 1‐g averaged SAR is lowered up to 0.0388 W/kg at 1 mm distance away from skin which is 98.3% less than that of only monopole.